PECULIAR FEATURES OF CASE APPLICATION IN THE DEVELOPMENT OF CULTURAL AND CREATIVE COMPETENCE OF LECTURERS OF HIGHER MILITARY EDUCATIONAL ESTABLISHMENTS - Жарова, Олена Валеріївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article is devoted to an actual problem of cultural and creative training of competent lecturers applying case technology in the system of higher military education. Based on the research of the problem under consideration, it has been established that the situational analysis technology presupposes students to be involved to the in-class substantive examination of specially designed cases containing real problem-based situations that may arise in the future professional activity. The author considers peculiar features of variously structured ‘dead’ and ‘live’ cases to be used in the development of cultural and creative competence of lecturers of the higher military educational establishment of Ivan Chernyakhovskyi National Defense University of Ukraine. On the ground of the material set forth, it has been proved that the application of cases, based on pedagogical situations and cultural and creative materials, ensures proper cultural and creative competence to be gained by the lecturers of higher military educational establishments, which allows them to quickly, comprehensively and flexibly solve professional issues, thus achieving efficient results in training military specialists